Margrave of the Marshes - Peel J. John (London, Corgi Books, 2006)
Through his musical taste which defined a culture and his wildly popular Radio 4 show, Home Truths, John Peel reached out to an audience that was as diverse as his record collection. This book, completed by the woman who knew him best, his wife, Shiela, presents an intimate portrait of his life, marriage and his family.